The Determinants of Credit Risk in Chinese Banks - Sun, Yu (2019)
The 2008 global financial tsunami made people realize the significance of banks’ credit risk. Therefore, it is meaningful to make a profound study on credit risk and this paper is aim to investigate the determinants of banks’ credit risk. In order to research the relationship between Chinese bank credit risk and the selected ten influencing factors involving macroeconomic determinants and bank-specific level factors, 149 listed Chinese commercial banks are chosen as data-set from 2012 to 2017 with panel data model. The sample of banks are classified into three types based on bank size of total asset, which are small scale banks, middle scale banks and large scale banks respectively. These three kinds of banks correspond to one of their respective models in Hausman test model. The results can help to improve the efficiency of credit risk management system of Chinese commercial banks. Moreover, the conclusion on which of the macro-economic and micro-economic determinants have significant explanatory power on credit risk of Chinese banks would be given.